PSYCHOLOGICAL-PEDAGOGICAL CHARACTERISTICS AND STRUCTURAL COMPONENTS OF THE DEVELOPMENT OF PROFESSIONAL CULTURE AMONG SCHOOL TEACHERS - Jumayeva Gulnora Tursunpulatovna (Zeta Repository, 2023)
The pursuit of excellence is a complex process that occurs along with the professional development of a person and continues almost throughout life. In a broad sense, professional development is manifested in connection with a specific area of human activity, as well as a specific profession, its values and worldview, mental and physical abilities, interests and actions.